Improving the life of sports workers: the impact of emotional labor on work engagement and well-being - Caetano, Patrícia de Jesus Pereira Tavares (2020)
With the present study, we intend to understand the impact of emotional labor in the wellbeing and work engagement of employees. Nevertheless, different types of emotional labor have different impacts in these variables. Moreover, it was analyzed the need for recovery as a mediator of this relations. After this review, it was also researched the impact of humor as a moderator between emotional labor in need for recovery, as well of recovery experiences between need for recovery, well-being and work engagement. In various public gymnasiums, there were collected 33 questionnaires, that were divided in two different moments, at the end of the workday, and at the beginning of the day after that. Results have supported a correlation of suppression with need and with impairedwell-being. However, when mediated by need for recovery, suppression does not only show to influence negatively well-being, but also work engagement. Furthermore, only emotional consonance appeared to have a significant influence on work engagement, being it positive. In conclusion, only suppression appears to have a significant impact in well-being and work engagement, even though need for recovery. Besides that, emotional consonance relates positively with work engagement. The moderation role of coworker humor and recovery experiences were not supported.